Analisis Pengaruh Kualitas Produk, Harga Produk, dan Orientasi Pasar Terhadap Kinerja Penjualan Pada UMKM Pengrajin Kayu di Gilingan Kota Surakarta - Saefudin, Ahmad, Dra. Mabruroh, MM (2016)
The aim of this study aimed to analyze the influence of the analysis of product quality, product prices, and market orientation to performance marketing in SMEs Gilingan craftsmen in Surakarta. The population in this study menggunan 76 respondents craftsmen in Gilingan Surakarta using the census is the collection of data, if all elements of the population investigated one by one. Data analysis methods used are bergand linear regression analysis and hypothesis testing using t-statistic, the F-statistic, and the coefficient of determination. From the analysis during the observation period t-test results showed that the quality of the product has a significant influence on the performance marketing, product pricing has a significant influence on the performance marketing, and market orientation has a significant influence on the performance marketing. F-test results found that the variable quality of products, product pricing, and market orientation together significant effect on marketing performance. Results obtained coefficient of determination adjusted R-square (R2) of 0.528, this means that 52.8% of the change or variation of marketing performance due to a change or variation of the variable quality of the products, product pricing, and market orientation. While 47.2% is due to changes in other variables not included in the variables studied. Keywords: sales performance, product quality, product rices, and market orientation